2005
DOI: 10.3748/wjg.v11.i37.5828
|View full text |Cite
|
Sign up to set email alerts
|

Strictures, diaphragms, erosions or ulcerations of ischemic type in the colon should always prompt consideration of nonsteroidal anti-inflammatory drug-induced lesions

Abstract: This uncontrolled retrospective study based on the histological finding of an ischemic necrosis shows that the histologically suspected diagnosis of NSAID-induced lesions in the colon is often correct. The true diagnostic validity of this finding and the differentiation from ischemic colitis should, however, be investigated in a prospective controlled study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 58 publications
1
19
0
3
Order By: Relevance
“…Colonic diaphragm-like strictures result from chronic use of sustained-release NSAIDs 1. NSAID-induced strictures were first described in 1989 2.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic diaphragm-like strictures result from chronic use of sustained-release NSAIDs 1. NSAID-induced strictures were first described in 1989 2.…”
Section: Discussionmentioning
confidence: 99%
“…Although Goldstein and Cinenza reported that none of their biopsy specimens from patients with NSAID-associated colitis showed histological features of ischemia [29], Yao et al reported one case of ischemic colitis identified by histopathological examination of NSAID-associated colitis [30]. Stolte et al reported no observable histological differences between NSAID ⁄ aspirin-induced lesions and ischemic lesions [24]. In the present study, because treatment with low-dose aspirin was not discontinued prior to undergoing colonoscopy in most cases, biopsy specimens were not taken during colonoscopy from patients treated with low-dose aspirin, as stipulated in the Japanese Guidelines for Prevention of Accidents during Colonoscopic Procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Sie in hibieren die Prostaglandinsynthese durch Hemmung der Zyklooxygenase und entkoppeln die mi tochondriale oxidative Phosphorylierung. Es kommt zu einer Verringerung von Adenosintriphos phat (ATP), zur Schädigung intrazellulärer Bindungen [3,4,5] und zur Freisetzung von vasokons triktiven Leukotrienen, freien Radikalen, Plättchenthromben und Proteasen. Es entsteht eine Stö rung der Mikrozirkulation und der Adhäsion von neutrophilen Granulozyten an das Endothel der kleinen Kapillaren.…”
Section: Pathomechanismusunclassified
“…Gerade bei älteren Patienten können Komplikationen ohne Warnsymptomatik auftreten. Die schwerwiegenden Komplikationen im unteren Gastrointes tinaltrakt sind Perforationen von Ulzera, verstärkte Blutungen und die Ausbildung von diaphragma tischen Stenosen vor allem im Colon ascendens [3,4,22]. In Fallberichten wird von einem longitu dinalen Ulkus über 20 cm Länge [23] oder auch tumorverdächtigen Ulzera [24] …”
Section: Dickdarmunclassified